Distinct modulation of allergic T cell responses by subcutaneous vs. sublingual allergen‐specific immunotherapy. Issue 3 (March 2016) - Schulten, V.; Tripple, V.; Aasbjerg, K.; Backer, V.; Lund, G.; Würtzen, P. A.; Sette, A.; Peters, B.
Summary: Background: Allergen‐specific immunotherapy is the only curative treatment for type I allergy. It can be administered subcutaneously (SCIT) or sublingually (SLIT). The clinical efficacy of these two treatment modalities appears to be similar, but potential differences in the immunological mechanisms involved have not been fully explored. Objective: To compare changes in the allergen‐specific T cell response induced by subcutaneous vs. sublingual administration of allergen‐specific immunotherapy (AIT). Methods: Grass pollen‐allergic patients were randomized into groups receiving either SCIT injections or SLIT tablets or neither. PBMCs were tested for Timothy grass (TG)‐specific cytokine production by ELISPOT after in vitro expansion with TG‐peptide pools. Phenotypic characterization of cytokine‐producing cells was performed by FACS. Results: In the SCIT group, decreased IL‐5 production was observed starting 10 months after treatment commenced. At 24 months, T cell responses showed IL‐5 levels significantly below the before‐treatment baseline. No significant reduction of IL‐5 was observed in the SLIT or untreated group. However, a significant transient increase in IL‐10 production after 10 months of treatment compared to baseline was detected in both treatment groups. FACS analysis revealed that IL‐10 production was associated with CD4 + T cells that also produced IFNγ and therefore may be associated with an IL‐10‐secreting type 1 cell phenotype. Conclusion and clinical relevance: The most dominant immunological changes on a cellular level were a decrease in IL‐5 in the SCIT group and a significant, transient increase of IL‐10 observed after 10 months of treatment in both treated groups. The distinct routes of AIT administration may induce different immunomodulatory mechanisms at the cellular level.